2019
DOI: 10.1590/s1984-296120180081
|View full text |Cite
|
Sign up to set email alerts
|

First report of antibodies to Neospora spp. in horses from Portugal

Abstract: Neospora spp. are intracellular protozoa with worldwide distribution and closely related to Toxoplasma gondii, which can infect a variety of mammals including horses. From September 2013 to June 2014, 185 horses from northern, central and southern parts of mainland Portugal were randomly sampled and tested for detection of immunoglobulin (Ig) G antibodies to Neospora spp. using an indirect multi-species enzyme-linked immunosorbent assay (ELISA) commercial test (ID Screen® Neospora caninum Indirect Multi-specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…These studies revealed considerable disparities in their findings. In Portugal, the seroprevalence rates were 1.1% using ELISA assays [21] and 9.1% using IFAT [28]. Similarly, in Italy, the seroprevalence rates were 2.3% using IFAT [17] and 11.8% using ELISA assays [27].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These studies revealed considerable disparities in their findings. In Portugal, the seroprevalence rates were 1.1% using ELISA assays [21] and 9.1% using IFAT [28]. Similarly, in Italy, the seroprevalence rates were 2.3% using IFAT [17] and 11.8% using ELISA assays [27].…”
Section: Discussionmentioning
confidence: 94%
“…The European studies included in this review were conducted in Italy [17,27] and Portugal [21,28]. These studies revealed considerable disparities in their findings.…”
Section: Discussionmentioning
confidence: 99%